Efficacy of a Core Strengthening Program for Diastasis Rectus Abdominis in Postpartum Women: A Prospective Observational Study. Issue 4 (18th October 2021) - Leopold, Madeline; Santiago, Kristen; Cheng, Jennifer; Keller, Leah; Abutalib, Zafir; Bonder, Jaclyn; Sharma, Geeta; Tenforde, Adam; Casey, Ellen
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Diastasis rectus abdominis (DRA) is characterized by a widening between the rectus abdominis muscles and thinning of the linea alba. It is common during pregnancy and may contribute to postpartum low back pain (LBP) and stress urinary incontinence (SUI). Core strengthening is thought to improve DRA, but there is no widely accepted exercise program. Objectives: To assess changes in interrectus distance (IRD) and participant-reported outcomes (PROs) after an online core strengthening program in postpartum women with DRA. Study Design: Prospective observational study. Methods: Forty-three postpartum women (36.7 ± 3.5 years) with DRA, which was diagnosed as an IRD 2.0 cm or more using musculoskeletal ultrasound, participated in a 12-week online core strengthening program focused on daily transversus abdominis activation with coordinated breathing and pelvic floor muscle engagement. IRD and PROs were assessed at baseline and 12 weeks. A subset of 19 women participated in an additional 12-week maintenance phase, and outcomes assessments were performed at 24 weeks. Results: The 12-week online core strengthening program significantly decreased IRD above and below the umbilicus at rest (slope [95% confidence interval]: −0.56 [−0.74, −0.38] and −0.26 [−0.45, −0.06]; P < .001 and P = .009, respectively) and below the umbilicus during contraction (−0.39 [−0.58, −0.20]; P < .001). Improvements in LBP-related disability ( P = .002) and SUI ( P = .001) were also observed. Participation in the maintenance phase significantly improved IRD at 24 weeks compared with 12 weeks ( P < .0125). Satisfaction averaged 7.43 ± 2.23. Conclusions: The 12-week online core strengthening program reduced IRD and improved LBP-related disability and SUI. Program participation for 12 additional weeks further reduced IRD. These results suggest that the online core strengthening program can be used in postpartum women with DRA.